EVALUASI DAMPAK PEMBELAJARAN ABAD 21 TERHADAP PENGEMBANGAN KARAKTER SISWA SEKOLAH DASAR - Raya Amanda Nur Islami; Rania Khairunnisak; Nandia Kiranti; Leli Halimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of elementary school students' character is a crucial aspect within the context of 21st-century education, which demands the implementation of innovative and holistic approaches to shape a generation with strong character and competence. This study combines quantitative and qualitative methods through observations, interviews, and questionnaires conducted in elementary schools implementing character-based and 21st-century competence-oriented learning models. Data were analyzed using descriptive statistics, correlation tests, thematic analysis, and source triangulation to ensure the validity of the findings. Results indicate that the application of character-based and 21st-century competence learning significantly enhances students' social, moral, affective, and personal aspects. Main supporting factors include teacher competence, supporting facilities, and a conducive environment, while major barriers involve stakeholder resistance and resource limitations. The main implication emphasizes the need for comprehensive school ecosystem strengthening through teacher training, facility support, and multi-stakeholder collaboration to ensure sustainability and effectiveness of the program. This study enriches educational literature regarding the implementation of character and 21st-century competence-based innovations at the primary education level and provides practical solutions for developing an adaptive and resilient educational ecosystem.